Foot Complications and Footwear Habits: A Study of Diabetes Mellitus Patients in Bangladesh - Haque, Md Sanaul; Enu, Yeaseer Arafat; Shahriar, Md Monem; Jor, Abu (Journal of Engineering Science, 2023)
Foot complications among diabetic mellitus patients are a major cause of morbidity and death across the world. A large number of Bangladeshis are also affected by this type of diabetes. This study aimed to explore the common foot complications and footwear selection of diabetes mellitus patients in Bangladesh. This study used a questionnaire to conduct empirical research and analyzed the data using statistics. In a survey of 304 diabetes mellitus patients, 36.84% reported peripheral neuropathy, 27.30% foot swelling, and 11.50% foot ulcers. Approximately 58.33% of patients reported at least one of the above complications. Only 14.5% of participants were aware of therapeutic footwear, and half were satisfied with their requirements. The remaining 85.5% of patients were careless about footwear safety. The findings of this study suggested increasing awareness of ergonomically fit footwear to reduce foot complications. Additionally, future studies should explore proper guidance and features for selecting and using them. Journal of Engineering Science 14(1), 2023, 77-83